The dyslexic adult : interventions and outcomes-- an evidence-based approach - McLoughlin, David, 1948- (Wiley, 2013)
A definitive and evidence-based guide for psychologists, teachers, coaches, HR personnel and all professionals who must understand and work with dyslexic adults. The only book to look at dyslexia within the context of life span developmental psychology, including the factors that contribute to success - now fully revised and updatedCombines an accessible style with a strong focus on evidence-based practice and a sound theoretical model on which to base assessment, counselling, teaching and trainingProvides a clear guide to the kinds of assessment that can be conducted.